Esperanza rising - Ryan, Pam Munoz. (Scholastic Press, 2000)
Esperanza and her mother are forced to leave their life of wealth and privilege in Mexico to go work in the labor camps of Southern California, where they must adapt to the harsh circumstances facing Mexican farm workers on the eve of the Great Depression.